PENGARUH PEMBERIAN KOMBINASI PUPUK ANORGANIK TUNGGAL DAN PUPUK HAYATI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) SERTA POPULASI MIKROBA TANAH - Darwin Habinsaran Pangaribuan; Kus Hendarto; Karisma Prihartini (Jurnal Floratek, 2017)
The aim of research was to determine the effect of the combination of a single inorganic fertilizers and biofertilizers on the growth and yield of sweet corn (Zea mays Saccharata Sturt) and soil microbial population. Research was conducted in Bandar Lampung from December 2015 to March 2016. The study was conducted using a randomized block design with six treatments and three replications. Those treatments were K0 (control), K1 (Urea 300 kg / ha, SP-36 150 kg / ha, KCl 100 kg / ha), K2 (Urea = 300 kg / ha, SP-36 150 kg / ha, KCl 100 kg / ha) + Biomax Grow, K3 (Urea 180kg / ha, SP-36 to 90 kg / ha, KCl = 60 kg / ha) + Biomax Grow K4 (Urea 60kg / ha, SP-36 30 kg / ha, KCl 20 kg / ha) and K5 = Biomax Grow. The experiment showed the highest production of sweet corn obtained was 13.20 tonnes / ha from a combination of 60% inorganic fertlizers with biofertilizer.